High anxieties : cultural studies in addiction - Brodie, Janet Farrell; Redfield, Marc, 1958- (Berkeley : University of California Press, 2002)
High Anxieties explores the history and ideological ramifications of the modern concept of addiction. Little more than a century old, the notions of "addict" as an identity and "addiction" as a disease of the will form part of the story of modernity.
Addiction and the ends of desire / Stacey Margolis -- A terminal case: William Burroughs and the logic of addiction / Timothy Melley -- Narrating national addictions: De Quincey, opium, and tea / Cannon Schmitt -- Victorian highs: detection, drugs, and empire / Marty Roth -- The rhetoric of addiction: from Victorian novels to AA / Robyn R. Warhol -- Firewater legacy: alcohol and Native American identity in the fiction of James Fenimore Cooper / Nicholas O. Warner -- Smoking, addiction, and the making of time / Helen Keane -- An intoxicated screen: reflections on film and drugs / Maurizio Viano -- Welcome to the pharmacy: addiction, transcendence, and virtual reality / Ann Weinstone -- If "reality is the best metaphor," it must be virtual / Marguerite Waller.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Substance abuse -- Social aspects; Drugs and literature; Drugs and motion pictures; Alcoholism in literature; Alcoholism in motion pictures; Virtual reality -- Social aspects; Polytoxicomanie -- Aspect social; Drogues et littérature.; Drogues et cinéma.; Alcoolisme dans la littérature.; Alcoolisme au cinéma.; Réalité virtuelle -- Aspect social; SOCIAL SCIENCE -- Customs & Traditions; SOCIAL SCIENCE -- Sociology -- General; Alcoholism in literature; Alcoholism in motion pictures; Drugs and literature; Drugs and motion pictures; Substance abuse -- Social aspects; Virtual reality -- Social aspects; Alcoolisme; Aspect social; Cinéma.; Drogue; Polytoxicomanie; Réalité virtuelle; Toxicomanie; Thème littéraire.; Thème.; Cultural studies; Illness & addiction: social aspects; Popular culture; Food and Drink